The Neural Correlates of Effortful Cognitive Processing Deficits in Schizophrenia: An ERP Study - Jiang, Chen-Guang; Wang, Jun; Liu, Xiao-Hong; Xue, Yan-Ling; Zhou, Zhen-He (Frontiers in Human Neuroscience, 2021)
Background: Individuals’ information processing includes automatic and effortful processes and the latter require sustained concentration or attention and larger amounts of cognitive “capacity”. Event-related potentials (ERPs) reflect all neural activities that are related to a certain stimulus. Investigating ERP characteristics of effortful cognitive processing in people with schizophrenia would be helpful in further understanding the neural mechanism of schizophrenia. Methods: Both schizophrenia patients (SCZ, n = 33) and health controls (HC, n = 33) completed ERP measurements during the performance of the Basic facial emotion identification test (BFEIT) and the Face-vignette task (FVT). Data of ERP components (N100, P200 and N250), BFEIT and FVT performances were analysed. Results: Schizophrenia patients’ accuracies of face emotion detection in the BFEIT and vignette emotion detection in the FVT were both significantly worse than the performance of the HC group. Repeated-measures ANOVAs were performed on mean amplitudes and latencies revealed that the interaction effect for group × experiment × site (prefrontal, frontal, central, parietal, and occipital site) was significant for N250 amplitude. In FVT experiment, N250 amplitudes at prefrontal and frontal site in schizophrenia group were larger than those of HC group; the maximum N250 was present at prefrontal site in both of groups. For N250 latency, the interaction effect for group × experiment was significant; N250 latencies in schizophrenia group were longer than those of HC group. Conclusion: Schizophrenia patients present effortful cognitive processing dysfunctions which reflect in abnormal ERP components, especially N250 at prefrontal cortex and frontal cortex sites. These findings have important implications for further clarifying the neural mechanism of effortful cognitive processing deficits in schizophrenia.